FATLIQUORING POTENTIALS OF SULPHONATED Lophira lanceolata SEED OIL AND ITS APPLICATION ON SHOE UPPER LEATHER - MAJU, C.C.; Z. LADAN; J. MICHAEL; I. AKAWU; I. AKAWU, (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2020)
Lophira lanceolata seeds were collected during the winter, dried and deshelled. The seeds were ground to smaller sizes to increase the surface area. N-hexane was used as the solvent for the extraction followed by the characterization and production of fatliquor. The following parameters were determined from the oil: solubility, acid value (AV), saponification value (SP), iodine value (IV), refractive index (RD) of the trial/control sulphonated oil and the results were observed to be 3.8 %, 204mgKOH/g, 74%, and 1.459 respectively. The functional groups were determined using Fourier Transform Infrared (FTIR). FT-IR analysis of the sulphated product confirmed the presence unsaturation (–C=C-). After the characterization, the oil was used for the production of sulphated fatliquor which was tested on three pieces of retanned goat skins divided along backbone line into two equal halves each. One half used as control while the other side used as a trial. The fatliquor was applied in the order of 3%, 5% and 7% and same percentages were used on the control samples. The leathers were dried, conditioned, staked, toggled and the following physical properties of the leather were examined for both trial and control samples: ball burst test, tensile strength, water absorption, percentage elongation and the results gave 3.48,3.27kg/mm,35.98,35.72 N/Mm2,40.21,40.90% respectively. The sulphonated Lophira lanceolata oil had good characteristics as a leather fatliquor as shown by the physical and strength properties of the fatliquored leather. The results obtained revealed that Lophira lanceolata can effectively be used to manufacture fatliquor to be used to lubricate leather in fatliquoring process. Keywords: Lophira lanceolata, oil, fatliquor and leathers.